Age- and sex-related differences in landmark recall following a virtual spatial navigation task - Chargo, Alexis N.; Dahle, Cheryl L.; Raz, Naftali; Daugherty, Ana M. (Frontiers in Aging Neuroscience, 2025)
IntroductionWayfinding is a cognitive ability that supports accurate spatial navigation and declines in this ability adversely affect independent living in older age. The cognitive map represents environmental details, such as landmark cues, relative to the goal location. Distal cues appear to be less effective than proximal ones in precisely locating the goal. Age-related declines in spatial precision may result in fewer accurate landmark-place details or hinder the differential use of cue types.MethodsThis study examined spatial navigation abilities using a virtual adaptation of the Morris Water Maze in a community lifespan sample of 169 adults (aged 18–78 years). Following 25 learning trials with a fixed, hidden platform, spatial precision of recalling the platform location was tested with map reproduction tasks that manipulated the environmental presentation of cues.ResultsAge-related differences varied by sex; middle-aged and older women were less precise in recalling platform location compared to men, but only when provided with all distal and proximal cues. This effect was partially related to the recall accuracy of landmark-place associations: middle-aged and older women who had recalled fewer details were less precise when provided all landmark cues. By comparison, the association between free recall and spatial precision was weaker in younger women and in middle-aged and older men.DiscussionThese findings suggest differential age- and sex-related variations in the integration of navigation cues in wayfinding.